Who was King Tut? /Biography-Easy reader - Edwards, Roberta; Kelley, True. (New York : Grosset & Dunlap, 2006)
Explains the life and times of this ancient Egyptian ruler, covering the story of the tomb's discovery, as well as myths and stories of mummy curses.
Who was King Tut? -- Gifts of the Nile -- An unusual father -- The boy king -- An early death -- Ready to die-the afterlife -- Mummy making -- Valley of the Kings -- Howard Carter -- Mummy mania -- Gold everywhere -- Meeting the king -- The legend lives on.
Includes bibliographical references (page 104)
Keywords: Tutankhamen, -- King of Egypt; Pharaohs -- Biography; Egypt -- Antiquities